Socio-cultural aspects of type 1 diabetes in Egypt: Where are we and where do we need to be? - Aly, Hanan Hassan (Journal of Social Health and Diabetes, 2013)
Socio-cultural factors play a pivotal role in the control of type 1 diabetes in children and adolescents, especially in developing countries like Egypt. The financial burden of this chronic illness, together with the modulations needed in lifestyle affect the family and school dynamics, adding further stress on the diabetic individual and his/her family. The key to improved outcome (not only in terms of glycemic control but also quality of life) has two arms. The first one is having a diabetes team with a psychologist skilled in this area for clear and positive communication with both the family and school from the time of diagnosis. The second one is the implementation of government laws to enforce the rights of diabetic children and adolescents.
Keywords: Children and adolescents; Egypt; family; government laws; psychologist; school; socio-cultural aspects; type 1 diabetes